1984
DOI: 10.1149/1.2115533
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Controlled and Transient Photocurrents of Photo‐Oxidation Reactions at Polycrystalline α ‐ Fe2 O 3

Abstract: Steady‐state photooxidation currents at polycrystalline α‐Fe2O3 electrodes with low band bending were found to depend significantly on the reducing agents present in the electrolyte. Photooxidation of water at low band bending exhibited only transient character. Diffusion‐controlled photocurrents for the photooxidation of I− and normalFefalse(CN)64− in acidic solutions, and OH− in unbuffered neutral solution were observed at an α‐Fe2O3 RDE and could be fitted to the Levich equation. The steady‐state and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…It has been reported that the conduction band of iron oxide by Mott-Schottky measurements is slightly above [30,31] and below [32,33] the H + /H 2 half-cell potential. The former claims were later confirmed by the report of Somorjai and Damme [21] who measured the flat-band potential of iron oxide varying between À0.9 and À1.1 V (vs. SCE) at pH 13.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the conduction band of iron oxide by Mott-Schottky measurements is slightly above [30,31] and below [32,33] the H + /H 2 half-cell potential. The former claims were later confirmed by the report of Somorjai and Damme [21] who measured the flat-band potential of iron oxide varying between À0.9 and À1.1 V (vs. SCE) at pH 13.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is a result of the relatively new use of semiconductor electrodes in electrochemical systems (13)(14)(15)(16), the kinetic complexity of photoelectrochemical current flow, and the diversity of properties found for different semiconducting materials (8) and for different crystals of the same semiconducting material. that control the rates of electrochemical reactions at metals (e.g., diffusion of solution species, reorganization energies, and double-layer effects) (1)(2)(3)(4)(5), the rates of photoelectrochemical reactions are affected by processes that occur within the electrode (e.g., carrier diffusion and recombination) and by the dependence of these processes on light intensity and photon energy (6)(7)(8)(9)(10)(11)(12). **Electrochemical Society Active Member.…”
mentioning
confidence: 99%
“…For example, the results given in Table I indicate that n = 2 fits the data reasonably well, and would be consistent with oxidation of S(III) in $2042-to S(IV) in SO~ 2-. [2] during analysis. Another alternative is seen in Eq.…”
Section: Resultsmentioning
confidence: 99%